Impact of e-cigarettes use on the oral health-related quality of life among young people in Metropolitan Lima - Fernando Vargas-Claudio; Olga Castilla- Minaya; Ximena Alejandra Leon-Rios (Universidad de Concepción., 2023)
Aim: To determine the effects of e-cigarette use on oral health-related quality of life (OHRQOL) in young people in Metropolitan Lima. Materials and Methods: This observational, analytical and cross-sectional study was performed with 189 individuals (age, 18-29 years) who used electronic cigarettes. The OHIP-Sp5 instrument was used to assess OHRQOL. Results: The use of e-cigarettes was higher among male participants (47.79%) than that among the female participants (26.32%). The mean OHRQOL scores of individuals who did and did not use e-cigarettes were 3.17 (2.26) and 3.12 (2.47), respectively These scores for people who did and did not use mouthwash were 2.92 (2.34) and 3.57 (2.43), respectively. Regarding orofacial pain 2.65% participants frequently re-ported "painful discomfort" and 7.41% of the young people presented such discomfort of orofacial aspect "frequently." Conclusions: Recording e-cigarette uses and frequency in patients' medical records is important, as well as incorporating educational strategies to reduce e-cigarette consumption and avoiding harmful effects on general health.